Soil Water Content Below 33.7% Progressively Reduces the Latex Yield of Rubber PB 60, A Study in Sembawa, South Sumatra, Indonesia - Ardika, Risal; Cahyo, Andi Nur (Department of Agronomy and Horticulture, IPB University, 2020)
Rubber is one of the economically important tropical trees that produces natural rubber, an essential industrial raw material in Indonesia. In general, rubber can grow well in areas with 1,500 - 3,000 mm rainfall per year that evenly distributed round the year. During the dry season, water availability is reduced so that water becomes a limiting factor for the growth and production of the rubber tree. This paper aimed to determine minimum soil water content that must be maintained to prevent the reduction of PB 260 rubber production based on field water balance. This research was carried out at the Indonesian Rubber Research Institute Experimental Field, South Sumatra, Indonesia, between 2014 to 2019. This experiment used PB 260 clone which was planted in 2001 using a 6 x 3 m plant spacing. Soil analysis showed that the Sembawa had a clay loam soil texture. The measured parameters were latex production (kg per ha per year), rainfall, and evapotranspiration (mm). The results from our six years of study showed that rubber production always decreased when soil water content started to decline below field capacity (33.7 %, or equal to 337 mm with 1m depth of root zone).